Sigmoid Diverticulitis and Perforation Secondary to Biliary Stent Migration - Margaret Riccardi; Kaitlin Deters; Furrukh Jabbar (Case Reports in Surgery)
Introduction. Biliary stent migration occurs in 5-10% of patients. Generally, this is a benign process and stents pass or are retrieved endoscopically. In rare instances, intestinal perforation has occurred. Presentation of Case. A 79-year-old female presented with a one-day history of abdominal pain. She had undergone an ERCP four weeks previously for primary choledocholithiasis during which time a sphincterotomy and sphincteroplasty were performed, and stents were placed in the common bile duct. CT scan of the abdomen and pelvis demonstrated a biliary stent that had migrated into the sigmoid colon, appearing to perforate the colon with free air throughout the abdomen. Patient was taken for diagnostic laparoscopy and noted to have biliary stent perforating the sigmoid colon. Procedure was converted to open, and Hartmann’s procedure was performed with end colostomy. Conclusion. Generally, biliary stent migration is a benign process, but in rare instances, intestinal perforation has occurred. Sites of perforation include the duodenum, distal small bowel, and colon. Perforation is more common with an additional pathology present such as hernias or diverticular disease. Migration and perforation also appear more common with straight biliary stents. In patients with known diverticular disease and straight biliary stents, considerations should be made for early stent removal.